ANALYSIS OF THE CHARACTERISTICS AND DEVELOPMENT DISPARITIES AMONG DISTRICTS/CITIES IN EAST NUSA TENGGARA PROVINCE - Sagajoka, Estherlina; Banda, Falentina Lucia (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2019)
This study aims to review the regional characteristics and the development disparities among districts/cities in East Nusa Tenggara Province. This quantitative descriptive study used the Klassen typology and Williamson index using PDRB time-series data per capita and economic growth rate during 2013-2018. The analysis of Klassen typology shows that Kupang City, East Flores Regency, Sikka Regency, and Ende Regency include the developing and fast-growing regions. Kupang Regency, Timur Tengah Selatan Regency, East Sumba Regency include in the developing, but depressed regions. Belu Regency, Alor, Lembata, Manggarai, Ngada, West Manggarai, Rote Ndao, East Manggarai, Southwest Sumba, Malacca, Nagekeo, Central Sumba, and Sabu Raijua District including in the potential and fast-growing areas, while West Sumba Regency and Regency North Middle East are categorized in the underdeveloped regions. The calculation of the Williamson Index of districts/cities in East Nusa Tenggara Province is approximately 0.0 - 0.11 in every district. This shows that the revenue of East Nusa Tenggara Province is evenly distributed in every district, except Kota Kupang which of value is nearly 1, which is 0.63%. This reflected that the revenue of Kupang City is not evenly distributed compared to other districts in Nusa Tenggara Timur Province.